Леди Л.: романы : перевод с французского / Ромен Гари - Гари Ромен (Женская библиотека. Камея, 1992)
Экземпляры: ф.7 (1993) / Инвентарный номер: 36709 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: Г 20 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44